A Study on Integrating Water Element in Preschool to Enhance Learning Environment for Children - Cheng, Jia Ying; Abdul Aziz, Zalena (MAJ - Malaysia Architectural Journal, 2020)
The education system and the physical learning environment for children has a mutual relationship to boost children’s development but the design of a kindergarten in Malaysia are restricted. The objective of this research study is to identify the possibility of water integrated design and the water-cooling strategy which is suitable to be designed in the kindergarten. A proper-planned space should have the integration of fun element which could trigger the children senses. Water is one of the elements which can stimulate the senses of human as it has a lot of potentials to be integrated into every part of the building. The availability of water helps to enhance environmental sustainability by cooling the indoor air temperature instead of having air-conditioned space. In this research study, a few precedent studies are selected to review and compare the way of integration of water in a child-friendly environment. Throughout the study, the water element has a lot of potentials to be integrated into kindergarten and could enhance certain sustainability